Women Status According to Spinoza and Kant's Thought - Fatemeh Bakhtiyari (Journal of Philosophical Investigations, 2020)
Spinoza, Dutch philosopher of the seventeenth century, and Kant, the hero of enlightenment, have dealt with women and their differences with men in their works. In a few places, Spinoza pointed out the matter of women and the sexual difference between people. Among Spinoza's works, there is no work that talks about just this matter. However, in the case of Kant, there are some works on this matter. Dealing with the matter of women and their social states according to these European philosophers of modern time, this essay tried to find out the similarities and differences of their attitudes. Thus, it has resulted that although their similar attitudes on the case of women, Spinoza's philosophy has some features which have made it the source and supporter of feminist philosophers and saved it from severe criticism of feminists have been proposed against Kant.